NOMA-Based ALOHA Protocol for Air-to-Ground Communications With Maximum Transmit Power Limits - Choi, Hyun Ho; Kang, Kyu Min; Lee, Howon (IEEE Internet of Things Journal, 2024)
Nonorthogonal multiple access (NOMA) techniques can recover collided signals simultaneously transmitted from different users that select different target received signal strength (RSS) levels. In this study, we apply NOMA to the slotted ALOHA protocol in an air-to-ground communication environment, where multiple unmanned aerial vehicles (UAVs) attempt random access to a ground control station (GCS). In such a wide airspace, the channel gain from UAVs to the GCS exhibits significant disparities and thus the UAVs far from the GCS are restricted to selecting lower target RSS levels due to the practical limitation on the maximum transmit power of UAVs. This limitation increases the probability that UAVs will choose lower target RSS levels and leads to a fairness issue between near and far UAVs. To address this challenge, we enhance the basic NOMA-ALOHA protocol in which the number of UAVs selecting each RSS level is adjusted and the probability of selecting each RSS level is determined in order that the selected RSS levels are distributed as evenly as possible. Subsequently, we present the operation of the proposed NOMA-ALOHA protocol between the GCS and UAVs and analyze the throughput of NOMA-ALOHA protocols, taking into account the impacts of the maximum transmit power limit and our adjustment algorithm. Analysis and simulation results show that the proposed NOMA-ALOHA improves both throughput and fairness performances against the conventional NOMA-ALOHA and also enhances the tradeoff between throughput and coverage in air-to-ground communication environments with a maximum transmit power limit.
Keywords: Air-to-ground communications; ALOHA; Atmospheric modeling; Multiple access; Non-orthogonal; Non-orthogonal multiple access; Power limit; Random access; Transmit power; Transmit power limit; Uplink; Air-to-ground communication; ALOHA; nonorthogonal multiple access (NOMA); random access; transmit power limit